Human Rights and Political Advertising Regulations in the European Union - Karunian, Alia Yofira (Kertha Patrika; Vol 45 No 3 (2023), 2023)
In the Political advertising, and the AdTech industry that powers it, have been raising concerns about data protection, potential manipulation, and selective information exposure to voters in the European Union. Against this backdrop, this article aims to answer the following question: What are the human rights implications of political advertising, and to what extent does the European Union’s regulatory framework address these problems? Research method applied in this article is normative legal research, using a combination of statutory and critical analytical approach. In conclusion, sectoral regulations in the election and political advertising, strengthened by comprehensive data protection regulations, are essential to mitigate the harm political advertising on online platforms causes.